Morphology and phylogeny of Atrocalyx acervatus sp. nov. (Lophiotremataceae) from Acer species - de Silva, Nimali I.; Thambugala, Kasun M.; Jeewon, Rajesh; Phookamsak, Rungtiwa; Goonasekara, Ishani D.; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2018)
A new species of Atrocalyx (Lophiotremataceae) was collected from dead branches of Acer species in Yunnan Province, China. This is the first record of Atrocalyx on Acer. Lophiotrema bambusae and Lophiotrema guttulata is transferred to Atrocalyx based on combined SSU, ITS, LSU and tef1 sequences analyses. A detailed description and illustration of the new species is provided, and two new combinations are proposed.